2020
DOI: 10.1002/jssc.201901040
|View full text |Cite
|
Sign up to set email alerts
|

Identification of components and metabolites in plasma of type 2 diabetic rat after oral administration of Jiao‐Tai‐Wan using ultra‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry

Abstract: Jiao‐Tai‐Wan, which is composed of Coptis Rhizoma and Cinnamon Cortex, has been recently used to treat type 2 diabetes. Owing to lack of data on its prototypes and metabolites, elucidation of the pharmacological and clinically safe levels of this formula has been significantly hindered. To screen more potential bioactive components of Jiao‐Tai‐Wan, we identified its multiple prototypes and metabolites in the plasma of type 2 diabetic rats by ultra high performance liquid chromatography/quadrupole‐time‐of‐fligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Recently, dietary factors that effectively enhance insulin sensitivity without any side effects represent a novel approach towards the treatment of metabolic disorders, such as diabetes and obesity. Therefore, the identification and characterization of bioactive compounds in edible plants, which could improve insulin sensitivity, are important for the treatment and prevention of type 2 diabetes [20, 21]. In the current study, a simple method of HPLC‐QTOF‐MS/MS was established to identify the phenolic compounds in R. meyeri leaves based on accurate mass and fragmentation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, dietary factors that effectively enhance insulin sensitivity without any side effects represent a novel approach towards the treatment of metabolic disorders, such as diabetes and obesity. Therefore, the identification and characterization of bioactive compounds in edible plants, which could improve insulin sensitivity, are important for the treatment and prevention of type 2 diabetes [20, 21]. In the current study, a simple method of HPLC‐QTOF‐MS/MS was established to identify the phenolic compounds in R. meyeri leaves based on accurate mass and fragmentation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…It also produced diagnostic fragment ions at m/z 320.0919 and 292.0973, which may be the fragmented ions generated by the continuous removal of a molecule of CH 4 and CO. Based on the comparison with the reference substance, it is unambiguously inferred that this compound is berberine (Figure 13b). According to the reference standard and existing literature reports (Kun et al, 2017; Li et al, 2020; Wang et al, 2019; Zhu et al, 2022), the structures of the remaining alkaloids could be identified similarly.…”
Section: Resultsmentioning
confidence: 94%
“…These substances may be metabolized to caffeic acid without detecting the prototype (Li et al, 2020), so the active ingredients include other quinic acid compounds identified in the Heigen extract, shown in Table 3.…”
Section: Targets Of Active Ingredients Of Heigen and Ramentioning
confidence: 99%
“…UHPLC-Q-Exactive Orbitrap MS is an efficiency and sensitivity technique to detect and identify chemical components or biological sample (Li et al, 2020), it can rapidly identify known metabolites by ccomparing experimental spectral data with databases (Ghane et al, 2022). Network pharmacology is an emerging research approach combined with pharmacology, bioinformatics, and network biology (Lin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%